1993
DOI: 10.1111/j.1600-0773.1993.tb00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of the K+ Channel Blockers 4‐Aminopyridine and Charybdotoxin on Sensory Nerves in Guinea‐pig Lung

Abstract: In the isolated guinea-pig bronchus, the potassium channel blocking agent 4-aminopyridine (10(-4) M) caused a contraction which was abolished by capsaicin tachyphylaxis, suggesting involvement of sensory neuropeptides. Charybdotoxin (10(-8), 5 x 10(-8) M), which is a potent blocker of the high-conductance Ca(2+)-activated K+ channel in smooth muscle, caused slowly developing and long lasting bronchoconstriction, which was resistant to capsaicin tachyphylaxis. Neither 4-aminopyridine (10(-3), 10(-4) M) nor char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…K ATP channel activators such as cromakalim also have cardioprotective properties and may be involved in ischaemic preconditioning (Rohmann et al, 1994, Gross et al, 1992. Our studies could not identify activation or blockade of K ATP channels as important factors in the release of CGRP, in spite of previous findings in the guinea-pig lung (Lou and Lundberg, 1993). Myocardial protection may not only be achieved by cardiac ischaemic preconditioning, but peripheral muscle ischaemia also induces myocardial protection through release of substances via humoral or neurogenic pathways (Birnbaum et al, 1997).…”
Section: Ion Channels Involved In the Release Of Cgrpcontrasting
confidence: 87%
See 1 more Smart Citation
“…K ATP channel activators such as cromakalim also have cardioprotective properties and may be involved in ischaemic preconditioning (Rohmann et al, 1994, Gross et al, 1992. Our studies could not identify activation or blockade of K ATP channels as important factors in the release of CGRP, in spite of previous findings in the guinea-pig lung (Lou and Lundberg, 1993). Myocardial protection may not only be achieved by cardiac ischaemic preconditioning, but peripheral muscle ischaemia also induces myocardial protection through release of substances via humoral or neurogenic pathways (Birnbaum et al, 1997).…”
Section: Ion Channels Involved In the Release Of Cgrpcontrasting
confidence: 87%
“…In addition, C-fibre activation with peptide release is enhanced after blockade of adenosine triphosphate-sensitive potassium channels (K ATP channels) (Lou and Lundberg, 1993). Interestingly, K ATP channels are involved in the local response to myocardial ischaemia, and potassium channel openers such as cromakalim seem to have an anti-ischaemic, Release and effects of calcitonin gene-related peptide in myocardial ischaemia 4 Scand Cardiovasc J Downloaded from informahealthcare.com by SUNY State University of New York at Stony Brook on 11/01/14 local cardioplegic effect (see Hearse, 1995).…”
Section: Physiology Of Cgrp Releasementioning
confidence: 99%
“…In addition, C-fibre activation with peptide release is enhanced after blockade of adenosine triphosphate-sensitive potassium channels (K ATP channels) (Lou and Lundberg, 1993). Interestingly, K ATP channels are involved in the local response to myocardial ischaemia, and potassium channel openers such as cromakalim seem to have an anti-ischaemic, local cardioplegic effect (see Hearse, 1995).…”
Section: Physiology Of Cgrp Releasementioning
confidence: 99%
“…It was reported that the activation of ChTX-sensitive K+ channels may be involved in the inhibitory modulation of peripheral nerves (Stretton et al, 1992;Lou & Lundberg, 1993), but the inhibitory effect of KW-4679 was not influenced by the presence of 10 nM ChTX or IbTX, a BKca channel blocker (Galvez et al, 1990). Since 30 nM ChTX and 100 nM IbTX induced contractions of the bronchial smooth muscle and augmented the EFS-induced contraction, we could not investigate the effect of ChTX at 30 nM and the effect of IbTX at 100 nM.…”
Section: Electrical Field Stimulation-induced Guinea-pig Bronchial Comentioning
confidence: 99%
“…It has been shown that the tachykinin-mediated response is inhibited presynaptically by the activation of several receptors such as the ,u-opioid receptor (Ray et al, 1991b), the CX2-adrenoceptor (Matran et al, 1989), the y-aminobutyric acid (GABA)B receptor (Belvisi et al, 1989;Ray et al, 1991a), the histamine H3 receptor ) the neuropeptide Y (NPY) receptor (Matran et al, 1989), the 5-hydroxytryptamine (5-HT) receptor (Broad et al, 1993) and the adenosine A2 receptor (Morimoto et al, 1993). It is reported that charybdotoxin (ChTX) prevented the inhibitory modulation by several agonists in the airway sensory nerves (Lou & Lundberg, 1993;Stretton et al, 1992). Hence it is suggested that activation of ChTX-sensitive intermediate and large conductance Ca2+-activated K+ channels (IKca channels and BKca channels, respectively) may be involved in the inhibitory modulation of the sensory nerves.…”
Section: Introductionmentioning
confidence: 99%